50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-260
|View full text |Cite
|
Sign up to set email alerts
|

MEMS Microphone Array on a Chip for Turbulent Boundary Layer Measurements

Abstract: A MEMS microphone array has been designed and applied to the measurement of wall pressure spectra under the turbulent boundary layer in flow duct testing at Mach numbers from 0 to 0.6. The array was micromachined onto a single chip in the PolyMUMPS surface micromachining process, allowing high spatial resolution and low surface roughness. The chip measures 1 cm by 1 cm, and is flush mounted into the wind tunnel wall. Individual elements are 0.6 mm in diameter, with element to element spacing of 1.11 mm in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Forest (2012) suggested that the dimensionless pinhole diameter d + should be smaller than 18 to ensure no sensor attenuation occurred for frequencies up to ω + = 1. The development of sensors based on microelectromechanical systems (MEMS) (Löfdahl, Kalvesten & Stemme 1996;Löfdahl & Gad-el Hak 1999;White et al 2012) is a possible way to obtain very small sensors with d + < 10. In SONOBL experiments, d + ∼ 45 and Corcos correction was used to obtain the autospectra up to ω + = 2.…”
Section: Discussionmentioning
confidence: 99%
“…Forest (2012) suggested that the dimensionless pinhole diameter d + should be smaller than 18 to ensure no sensor attenuation occurred for frequencies up to ω + = 1. The development of sensors based on microelectromechanical systems (MEMS) (Löfdahl, Kalvesten & Stemme 1996;Löfdahl & Gad-el Hak 1999;White et al 2012) is a possible way to obtain very small sensors with d + < 10. In SONOBL experiments, d + ∼ 45 and Corcos correction was used to obtain the autospectra up to ω + = 2.…”
Section: Discussionmentioning
confidence: 99%
“…was dedicated to the diaphragm perforation in acoustic short-circuit in a low acoustic pressure equalization. Others authors propose openings and perforation in diaphragm [8][9][10][11], but in their work either technology was not used [8,9], was not presented [10,11]. This paper is structured as follows.…”
Section: Mems Technology Acoustic Mems Front-mentioning
confidence: 99%
“…[13]. Arrays of MEMS microphones are specially designed for acoustic source localization [14]; however, they are also used in other applications such as speech processing [15], turbulence measurements [16], identifying geometric dimensions and internal defects of concrete structures [17], or acoustic imaging [18,19]. Due to the high diversity of the applications of these arrays, the authors widened these uses to another field, such as the industrial one [20].…”
Section: Introductionmentioning
confidence: 99%